Islamic banking development and access to credit - PUTRA, MUHAMMAD ARVIAN RIFANDA (Maliki Interdisciplinary Journal, 2025)
Islamic banking has become an important part of the global financial system, providing credit to more people, especially to groups marginalized by conventional banking. This article examines the development of Islamic banking and how it impacts access to credit, with particular emphasis on sharia-based financial products. Studies show that Islamic banking increases financial inclusion and social justice. However, problems such as lack of support for policies and lack of public understanding still exist. Therefore, more intensive education and closer cooperation between financial institutions and the government are needed to maximize the potential of Islamic banking for sustainable economic progress.